Peranan Guru Sekolah Minggu dalam Membangun Budaya Membaca dan Menulis - Ferry Yefferson Tulle (REDOMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Reading and writing is the first commandment that was revealed by God to humans, It is an encouragement to mankind to read meaningful books and books of life about successful characters both in the Bible and who are currently the owners of Science (written on natural events) through reading here's gonna be know. Living in an oral culture from year to year, unable to manage a reading and writing culture. It should be realized that making a personal library at home. Has the house held many books of knowledge for children? Children who are students and students, because books are knowledge that must be added to in order to get clear water of knowledge. The tradition of reading which has now been widely practiced in the world of formal education should also be cultivated wherever and whenever. Make books a good friend, at church at school or wherever we are. every month the money is set aside to buy books to save for children, so that children do not bother when children study at school, smart children answer questions from teachers at school can excel through reading, reading and writing. AbstrakMembaca dan menulis adalah perintah pertama yang diwahyukan Tuhan kepada manusia, Merupakan anjuran kepada umat manusia untuk membaca buku – buku bermakna dan buku kehidupan tentang tokoh yang telah sukses baik dalam Alkitab maupun yang pada saat ini sang pemilik Ilmu-tertulis pada kejadian alam) lewat membaca inilah akan menjadi tahu. Hidup dalam budaya lisan dari tahun ke tahun, tidak mampu mengelola budaya membaca dan menulis. Perlu disadari bahwa membuat perpustakaan pribadi dirumah.  Sudahkah rumah itu menyimpang banyak buku pengetahuan bagi anak – anak? Anak yang berstatus pelajar dan mahasiswa, sebab buku adalah ilmu yang harus terus ditimbah agar mendapatkan air jernih pengetahuan. Tradisi membaca yang kini telah banyak dilakukan di dunia pendidikan formal kiranya membaca buku juga harus dibudayakan dimanapun dan kapan. Jadikan buku sebagai teman yang baik, di gereja di sekolah atau dimana kita berada. setiap bulan dapat uang itu disisikan untuk beli buku menyimpan buat anak – anak, supaya anak – anak tidak repot saat anak – anak belajar di sekolah, anak – anak pintar menjawab pertanyaan dari guru di sekolah dapat berprestasi lewat baca membaca dan tulis menulis.